Warfarin doses for anticoagulation therapy in elderly patients with chronic atrial fibrillation - Antonio de Padua Mansur; Julio Yoshio Takada; Solange Desiree Avakian; Celia M.C. Strunz (Clinics, 2012)
OBJECTIVE: Anticoagulation is a challenge for the prophylaxis of thromboembolic events in elderly patients with chronic atrial fibrillation. Stable anticoagulation is defined as the time within >70% of the therapeutic range. However, the dosage required to achieve stable anticoagulation remains unknown. The aim of this study was to analyze the warfarin dose necessary for the maintenance of stable oral anticoagulation therapy in elderly patients. METHODS: We analyzed 112 consecutive outpatients with atrial fibrillation who were >65 years of age, had received anticoagulation therapy with warfarin for more than 1 year and had a stable international normalized ratio between 2.0 and 3.0 for >6 months. The international normalized ratio was measured in the central laboratory using the traditional method. RESULTS: The patients were stratified according to the following age groups: <75 or >75 years and <80 or >80 years. The mean daily doses of warfarin were similar for patients <75 or >75 years (3.34+1.71 versus 3.26 +1.27 mg/ day, p = 0.794) and <80 or >80 years (3.36+ 1.49 versus 3.15 + 1.23 mg/day, p = 0.433). In 88 (79%) patients, the daily warfarin dose was between 2 and 5 mg/day; in 13 (11%) patients, the daily warfarin dose was <2.0 mg/day; and in 11 (10%) patients, the daily warfarin dose was >5.0 mg/day. The correlation between the daily warfarin dose and the international normalized ratio was 0.22 (p = 0.012). CONCLUSION: Stable anticoagulation was achieved in 80% of patients who received doses of 2 to 5 mg/day of warfarin, and the mean daily dose was similar across the age groups analyzed.